Strategi Koping Masyarakat Dalam Kepatuhan Menjalankan Protokol Kesehatan Selama Pandemi Covid-19 - Endah Sari Purbaningsih; Darini; Muadi (LPPM ITEKES Mahardika, 2022)
The covid-19 pandemic is currently a serious problem in the world with the number of cases that are always increasing every day, so the government issues a health protocol policy in carrying out activities outside the home must comply with health protocols that include wearing masks, washing hands, maintaining distance, because of the policy people become panicked and physically anxious. The purpose of this study is to find out how the coping strategy of the Gembongan Mekar Village community in compliance with health protocols during the covid 19 pandemic. This type of research is quantitative with a correlational descriptive design with a cross sectional approach. The population in this study is the community of Gembongan Mekar Village, samples in this study as many as 88 respondents and sampling techniques in this study are using purposive sampling, instruments used in the form of questionnaire sheets, as well as data analysis using spearman rank tests. The results of this study show that there is a relationship between the coping strategies of the Gembongan Mekar Village community in compliance with health protocols during the covid 19 pandemic Spearman rank test results P Value < and r < 1. In this study presented as a program to provide posters or pamphlets as information about coping strategies in compliance with health protocols during the covid 19 pandemic to prevent and reduce covid 19 transmission